Impact of occupational safety and health Act 1994 towards labour demand by the manufacturing sector: a case study in Kuala Lumpur and Selangor - Rahmah Ismail; Lum, Heap Sum (Penerbit Universiti Kebangsaan Malaysia, 2000)
This article analyses the effects of labour market regulation, i.e., the Occupational Safety and Health Act (OSHA) 1994, and all its related regulations, on the demand for labour. The changes that these regulations induce in the technology and costs of production will affect labour demand in the manufacturing sector. The nation’s growth in manufacturing output and trade has prompted concern for the effect of economic growth on occupational safety and health at the workplace. Regulatory stringency is expected to increase in Malaysia. Arguments against regulations are often framed in terms of tradeoff between jobs and accident occurences. The results of this study showed that the indtroduction of OSHA 1994 has a significant impact on the demand for labour by firms. This study also shows that OSHA 1994 has different impacts on different types of industries in relation to labour demand